Climate-Smart Agriculture Investment Plans - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The approach has now been piloted in 4 countries by CIAT/ICRAF/CCAFS, with the approach being scaled out to at least 7 other countries.